2015
DOI: 10.1080/09593330.2015.1026285
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bisphenol derivatives through quinone oxidation by polyphenol oxidase and subsequent quinone adsorption on chitosan in the heterogeneous system

Abstract: In this study, the combined use of a biopolymer chitosan and an oxidoreductase polyphenol oxidase (PPO) was systematically investigated for the removal of bisphenol derivatives from aqueous medium. The process parameters, such as the pH value, temperature, and PPO concentration, were estimated to conduct the enzymatic quinone oxidation of bisphenol derivatives by as little enzyme as possible. Bisphenol derivatives effectively underwent PPO-catalysed quinone oxidation without H2O2 unlike other oxidoreductases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Chitosan along with polyphenol oxidase were used in conjunction for eliminaton of bisphenol derivatives from aqueous solutions based on adsorption of enzymatically generated quinine derivatives on chitosan beads or chitosan powders. The optimum temperature and pH conditions were 40 °C and pH 7 for bisphenols B, E, O, and Z; 30 °C and pH 7 for bisphenols C and F; and 40 °C and pH 8 for bisphenol T. The removal time could be reduced by using more chitosan beads or chitosan powders of a smaller size [ 135 ]. Sorption of Cd(II) ions onto cross-linked low-molecular-weight chitosan pyruvic acid derivative followed Langmuir isotherm model and displayed pseudo second-order kinetics.…”
Section: Applicationsmentioning
confidence: 99%
“…Chitosan along with polyphenol oxidase were used in conjunction for eliminaton of bisphenol derivatives from aqueous solutions based on adsorption of enzymatically generated quinine derivatives on chitosan beads or chitosan powders. The optimum temperature and pH conditions were 40 °C and pH 7 for bisphenols B, E, O, and Z; 30 °C and pH 7 for bisphenols C and F; and 40 °C and pH 8 for bisphenol T. The removal time could be reduced by using more chitosan beads or chitosan powders of a smaller size [ 135 ]. Sorption of Cd(II) ions onto cross-linked low-molecular-weight chitosan pyruvic acid derivative followed Langmuir isotherm model and displayed pseudo second-order kinetics.…”
Section: Applicationsmentioning
confidence: 99%
“…The appearance of the absorbance at 400 nm showed that the alkylphenols used underwent PPO-catalyzed quinone oxidation in the same manner as the case when mushroom and Aspergillus tyrosinases were used [20,21,22,23,33,34]. This meant that the catechol intermediates were converted into the corresponding quinone derivatives by the catecholase activity of PPO.…”
Section: Resultsmentioning
confidence: 98%
“…Effects of enzyme concentration on PPO-catalyzed quinone oxidation of 14 kinds of linear and branched alkylphenols were investigated at pH 7.0 and 40 °C (Table 1). These values were determined as the optimum conditions of PPO used in this study for BPA and its derivatives in our previous articles [33,34]. Therefore, these optimum conditions were used for PPO-catalyzed quinone oxidation in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations